Health Status of Rubber Tree Farmers in Tambon Khok Kong, Bueng Kan District, Nong Khai Province - Nookaew, Preedasak; Aunjai, Dowrueng (Journal of Health Science of Thailand, 2017)
This study was aimed at observing health status of rubber tree farmers in Tambon Khok Kong, Bueng Kan District, Nong Khai Province. From the sample of 254, the data was systematically randomized and collected by interviewing with the questionaire reliability of 0.90. The data was collected throughout July 10th - August 24th, 2010. The statistical test applied in this study included percentage, average, standard deviation, mean, maximum, minimum, independent sample ttest, and one-way ANOVA. The couple differentiation was determined by LSD with the significantl level of 0.05. The result showed that dominant gender was male (66.5%) with the average age of 39.28 years (SD 8.32). While 90.2 percent of them were married. 58.7 percent had primary education level with an average income of 18,206.67 THB per month. Yet 77.2 percent were in debt within the range lower than 100,000 THB, of which 83.7 percent had legal obligation. It was found that 90.9 percent of them worked every two other days. The routine works included knife sharpening (94.9%), slitting (99.6%), acid pouring (95.3%), chemical fertilization (65.0%), sulfuric acid usage (56.3%), and herbicide-absorbing chemical usage (45.3%). Mostly, the plantations were far away from their living place (58.7%). Average working hours were 4.06 hours (SD 1.90 hours).While 56.3 percent had second job, while 57.9 percent also belonged to or participated in groups or fund. Overall health status was good (mean 2.47, SD 0.25). In addition, health status and educational level, obligation, number and type of obligation, frequency of work, herbicide usage, type of herbicide, distance between field and living place, obstacle at work, and group membership were significantly different (p 0.05) This study suggests that there should be the properly active approach strategy for rubber tree farmers in specific area.